Successful stenting of systemic venous pathway stenosis after double switch repair for congenitally corrected transposition of great arteries in a child - Arda Saygılı; Yusuf Yalçınbaş; Ahmet Aranz; Tayyar Sarıoğlu (KARE Publishing, 2014)
An 8-year-old boy with previous shunt operation for corrected transposition of great arteries, ventricular septal defect, pulmonary stenosis and multiple aortopulmonary collateral arteries underwent corrective surgery. In the early post-operative period, there were clinical findings of superior vena cava obstruction. Cardiac catheterization at 72 h following surgery showed a systemic venous baffle stenosis between the vena cava and right atrium. A stent was successfully implanted in the vena cava percutaneously, and the stenosis was relieved. Her symptoms resolved in a short time period, and she was extubated rapidly. During the follow-up, excellent maintenance and patency of systemic venous baffle were observed.